CABA-V7: a prospective biomarker selected trial of cabazitaxel treatment in AR-V7 positive prostate cancer patients. (December 2022) - Isebia, Khrystany T.; Mostert, Bianca; Belderbos, Bodine P.S.; Buck, Stefan A.J.; Helmijr, Jean C.A.; Kraan, Jaco; Beaufort, Corine M.; Van, Mai N.; Oomen - de Hoop, Esther; Sieuwerts, Anieta M.; van IJcken, Wilfred F.J.; van den Hout - van Vroonhoven, Mirjam C.G.N.; et al.
Abstract: Background: Metastatic castration-resistant prostate cancer (mCRPC) patients with positive AR-V7 expression in their circulating tumour cells (CTCs) rarely derive benefit from abiraterone and enzalutamide. Design: We performed a prospective, multicenter, single arm phase II clinical trial (CABA-V7) in mCRPC patients previously treated with docetaxel and androgen deprivation therapy. Objective: In this trial, we investigated whether cabazitaxel treatment resulted in clinically meaningful PSA response rates in patients with positive CTC-based AR-V7 expression and collected liquid biopsies for genomic profiling. Results: Cabazitaxel was found to be modestly effective, with only 12% of these patients obtaining a PSA response. Genomic profiling revealed that CTC-based AR-V7 expression was not associated with other known mCRPC-associated alterations. CTC-based AR-V7 status and dichotomised CTC counts were observed as independent prognostic markers at baseline. Conclusions: AR-V7 positivity predicted poor overall survival (OS). However, cabazitaxel-treated AR-V7 positive patients and those lacking AR-V7 positivity, who received cabazitaxel as standard of care, appeared to have similar OS. Therefore, despite the low response rate, cabazitaxel may still be an effective treatment in this poor prognosis, AR-V7 positive patient population. Highlights: AR-V7 is observed to be an independent prognostic marker in mCRPC. No association of AR-V7 status to mCRPC-associated alterations. PSA response rate of 12%, primary end-point therefore not met. Cabazitaxel may still improve prognosis in AR-V7 positive patient population.